PESAN MORAL PADA FALSAFAH MOH LIMO SUNAN AMPEL DALAM BUKU “MENJADI PRIBADI NU IDEAL?” - Raden Muhamad Mukhtar Ghozali; A. Khairuddin; M.Syakur (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
Globalization creates barriers between ethnic, cultural, social and religious. Responding to these barriers, it is necessary to re-understand Sunan Ampel’s efforts to change the morality of the Majapahit people in Ampel Denta into a more civilized society by using the philosophy of moh limo at that time. The purpose of this study is to describe the moral message contained in the philosophy of moh limo Sunan Ampel in the book “Being an Ideal NU Person?”. In this study, researchers used qualitative research with a library study research model. The results of the study show that there are five moral messages in the philosophy of moh limo Sunan Ampel in the book “Being an Ideal NU Person?”. moh main (don’t gamble), moh ngumbih (don’t consume liquor), moh madat (don’t consume narcotics), moh maling (don’t steal) and moh madon (don’t commit adultery).